2020
DOI: 10.3390/metabo10060259
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Metabolomic and Lipidomic Candidates for Biomarkers in Radiation Injury

Abstract: A large-scale nuclear event has the ability to inflict mass casualties requiring point-of-care and laboratory-based diagnostic and prognostic biomarkers to inform victim triage and appropriate medical intervention. Extensive progress has been made to develop post-exposure point-of-care biodosimetry assays and to identify biomarkers that may be used in early phase testing to predict the course of the disease. Screening for biomarkers has recently extended to identify specific metabolomic and lipidomic responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 104 publications
6
22
0
Order By: Relevance
“…The following are the most frequently altered metabolites in response to different doses of radiation (wide dose range with varying dose rates and different qualities) exposure that have been detected and validated in various animal models and in clinical patient samples: carnitine [11,[15][16][17][18][19] .…”
Section: Metabolites As Biomarkers For Radiation Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…The following are the most frequently altered metabolites in response to different doses of radiation (wide dose range with varying dose rates and different qualities) exposure that have been detected and validated in various animal models and in clinical patient samples: carnitine [11,[15][16][17][18][19] .…”
Section: Metabolites As Biomarkers For Radiation Injurymentioning
confidence: 99%
“…As a result of a decrease in glycolysis and tricarboxylic acid activity, succeeding pathways were also dysregulated (decreased fatty acid oxidation and increased ketogenesis) [34] . Creatinine and uric acid have been shown to decrease in response to irradiation in various animal models [16] . Several studies have demonstrated decreased circulating citrulline levels in murine and NHP models following irradiation [12,35,36] .…”
Section: Metabolites As Biomarkers For Radiation Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Protocols routinely used for the preparation of samples including for liquid chromatography mass spectrometry (LC-MS) metabolomic analysis were published by Laiakis et al [21], as was a method which allows for the possibility of rapid preparation protocols for blood [113]. Vincente et al [29] recently published a detailed tabulation of different metabolite trends from various biosamples across multiple species, radiation doses, and time-points.…”
Section: Types Of Metabolomic Samplesmentioning
confidence: 99%
“…That review concluded that metabolomics had the potential to serve as an important means of accurately assessing radiation exposure. More recent reviews by Menon et al [28], Roh [20], and Vincente et al [29] have highlighted recent advances in radiation metabolomics as applied to biodosimetry. However, the metabolomics approach is a behemoth, with its own set of challenges ranging from specifics of sample preparation, technology and analysis employed, to the interpretation of output data and translation [30].…”
Section: Introductionmentioning
confidence: 99%